Reconstructive plastic surgery in patients with complex defects and deformities of the head when removing extracerebral tumors extending beyond the cerebral skull - Morozov Tenhiz А.; Kvasha, Michail S. (Ukrainian Neurosurgical Journal, 2022)
Objective: To improve the surgical results of neurosurgical patients with complex defects and deformities of the head based on modern innovative technologies. Маterials and methods. Based on the analysis of diagnosis and surgical treatment of 54 patients with common extracerebral tumors of the head the issues of optimizing their treatment were considered. The positive role of reconstructive-plastic operations in complex defects and deformities of the head on the basis of modern possibilities of computer modeling and use of arterial autografts is noted. Results. Carrying out computer simulations before the operation, radical removal of the tumor with a single-stage reconstructive-plastic operations with the use of innovative technologies provides high efficiency of treatment, satisfactory quality of life of patients. Conclusions. Reconstructive plastic surgery in patients with complex defects and deformities of the head when removing extracerebral tumors that extend beyond the cerebral skull, can provide a satisfactory functional and cosmetic effect of the operation. Radical removal of the tumor by a single-stage autologous tissue grafting using modern technologies promotes rapid wound healing and good quality of life. In patients with widespread cancer stages of the skull, for the plasty of complex soft tissue defects of the cranial vault, the optimal operation is the use of regional musculocutaneous flaps. The type, shape and required amount of the tissue depends on the size and location of the defect. It has been confirmed that the use of a horizontal D-shaped musculocutaneous flap is justified for temporal and parietal defect plasty, and the use of a vertical D-shaped musculocutaneous flap is required to close the occipital-parietal defect. The use of computer simulation is effective and appropriate in patients with large defects and deformities of the cerebral and facial skull when planning complex reconstructive plastic surgery. The use of modified surgical approaches, the latest innovative technologies has made it possible to significantly improve the quality of life of patients, contributed to their early rehabilitation and readaptation.